(untitled) (Research Nepal Journal of Development Studies, 2024)
Nepalese Buddhism has historically influenced rural development, particularly in the Himalayan belt, where monastic institutions, religious values, and community practices intersect with socio-economic initiatives. This review synthesizes the historical evolution, doctrinal foundations, and thematic roles of Buddhism in rural development across Himalayan communities, including Solukhumbu, Mustang, and Dolpo. Using a mixed chronological and thematic literature review methodology, it examines Buddhist contributions to social capital, education, local economies, community-based tourism, gender equity, and environmental stewardship. Real case studies highlight monastic-led development programs and indigenous practices. The review identifies gaps in longitudinal research, interdisciplinary studies, and policy integration, offering directions for sustainable rural development strategies informed by Buddhist principles.